PEMBELAJARAN SELAMA PANDEMI KELOMPOK A DI PAUD DEHASEN KOTA BENGKULU (Deskriftif kualitatif di PAUD Dehasen Kota Bengkulu) - Ilda Juli Tri; Ranny Fitria Imran; Novi Ade Suryani (Early Childhood Research and Practice, 2022)
This study aims to find outthe application of learning during the pandemic 19 via online to early childhood in group A of PAUD Dehasen in Kebun Tebeng Ratu Agung sub-district as an educational service during the COVID-19 emergency response period. The subjects of this study were the principal, teachers, group A, and parents from group A with a total of 5 people. Primary data were obtained through in-depth interviews with research subjects who continued with observation and documentation as the initial process of further analysis, analyzed by reducing and classifying data. such as the analysis is narrated descriptively and concluded according to the question formulation of the problem. Through the stages of planning objectives, materials, implementation, and evaluation of online learning using the WhatsApp application that is part of the WhatsApp Group class A. The online learning implementation includes opening activities, core activities, display techniques and knowledge sharing. And the last stage is the online learning evaluation stage. which contains an assessment of the results of children's activities sent via video, photos, and voicenotes and used as the basis for daily, weekly, monthly and end of semester assessments.